Analisis Klaster Kependudukan di Kota Blitar Menggunakan Metode Fuzzy C-Means Clustering - Yumna Salsabila Firdaus; Rachmadania Akbarita; Rizka Rizqi Robby (Jurnal Matematika, 2022)
Blitar City is one of 9 cities in East Java province with an area of 32.58 km2, and has an unequal population distribution in every urban village. There is a difference of 11,719 people between urban villages that have a dense population and a small population. The purpose of this study is to analyze clusters or categorize the population of 21 urban villages in Blitar City by population migration factors, births and mortality. In this study using secondary data obtained from the Blitar City Statistics Centre, namely demographic data in 2019. The methodology used in this study is Fuzzy C-Means (FCM) cluster analysis. FCM is a cluster method in which the existence of each data in a cluster is determined by the degree of membership based on fuzzy logic theory. This method was chosen because it makes it possible to group data that is scattered irregularly. Create a convergent cluster centre using the objective function. The test results were then validated using Partition Entropy, Partition Coefficient and Pseudo F. There were many clusters = 2, 22 iterations, with an objective function of 98252.44. There are 14 urban villages in Group Cluster 1 and 7 urban villages in Cluster 2.